Carbon nanodots crosslinked photoluminescent alginate hydrogels. Issue 79 (30th October 2017) - Wijayapala, Rangana; Hashemnejad, Seyed Meysam; Kundu, Santanu
Abstract : Multicolor, fluorescent, stable, alginate hydrogels are synthesized by crosslinking alginate chains with phenylenediamine based carbon nanodots. Abstract : Alginate hydrogels are commonly used in biomedical applications and these hydrogels are usually prepared by ionic or covalent crosslinking. This study reports a new synthesis route for preparing photoluminescent alginate hydrogels using amine functionalized carbon nanodots (CNDs). CNDs with amine functional groups have been synthesized from ortho, para, and meta phenylenediamine by using the solvothermal method. The nanodots display yellow, red, and blue color when excited with a UV light with the wavelength of 365 nm. Amine groups on the CNDs form chemical crosslinks with alginate chains leading to the formation of a crosslinked network. The sol-to-gel transition has been monitored by using in situ shear rheometry. The CNDs crosslinked hydrogels maintain their fluorescent activity in a phosphate-buffered saline solution for a prolonged duration. Stable hydrogels with photoluminescent activity will have potential applications in metal ions sensing, drug delivery, and other biological applications.